Job Satisfaction and Burnout among Nurses Working in Critical Care Units - Al-Marhoon, Fatimah Mahdi; Al-Ammar, Mlake Zaki; Alzuraiq , Reem Salem; Almowallad, Ebtihal Abdulali; AL MURAIBUT, SAKNAH KHALED; Almuraibit, Zainab Khalid; aldagham , Mariyam Eassa; Alsaihati, Sarah Mohammed Hassan; Alanizi , Dana Naif; Hazazi , Sadaa Ahmed; Bahakeem, Abrar Faisal Ahmed; Alkathiri, Abdullah Saleh (Journal of Ecohumanism, 2024)
Background: Burnout among critical care nurses is a growing concern due to the high-stress environment of Intensive Care Units (ICUs). Understanding how these professionals cope with stress and how it impacts their job satisfaction is essential for improving workplace well-being and patient care outcomes. Objectives: This study aimed to examine the levels of burnout among critical care nurses, identify their coping strategies, and explore the relationship between these variables and job satisfaction. Methods: A cross-sectional study was conducted with 620 critical care nurses recruited through convenience sampling from multiple healthcare facilities. Data were collected using validated self-report questionnaires: the Maslach Burnout Inventory (MBI) to assess burnout, the Ways of Coping (WOC) scale to identify coping mechanisms, and the Job Satisfaction Scale (JSS) to evaluate overall job satisfaction. Statistical analyses, including descriptive statistics, factor analysis, and ordinal logistic regression, were performed using SPSS (version 22.0). Results: The majority of participants were female (83.9%), with diverse demographic backgrounds. Emotional exhaustion and depersonalization were significantly associated with lower job satisfaction. Factor analysis confirmed the multidimensional nature of coping, revealing a predominant use of emotion-focused strategies. Ordinal logistic regression identified key predictors of burnout, including coping style, satisfaction levels, and demographic factors. Conclusions: High levels of burnout were observed among ICU nurses, particularly among those using maladaptive coping strategies. Job satisfaction emerged as a protective factor. These findings underscore the need for targeted interventions to promote effective coping and enhance job satisfaction, which could reduce burnout in high-stress healthcare environments.